2012
DOI: 10.1002/acp.2827
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Effects of Monitoring Popular Films for Historical Inaccuracies

Abstract: History educators often use popular films in the classroom to teach critical thinking through an exercise that involves identifying historical inaccuracies in the films. We investigated how this exercise affects the acquisition of true and false historical knowledge. In two experiments, subjects studied texts about historical topics and watched clips from corresponding films. Each film contained one piece of information that contradicted the text (i.e. misinformation). Some subjects received instructions to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…For example, it may be affected by the text genre (narrative vs. expository texts) or by the perceived credibility of a text source (encoding under distrust; e.g., Schul, Mayo, & Burnstein, 2004). For 22 ISBERNER AND RICHTER example, people seem to be particularly susceptible to false information and persuasion when reading or viewing narratives (e.g., Appel & Richter, 2007;Gerrig & Prentice, 1991;Green & Brock, 2000;Umanath, Butler, & Marsh, 2012), which suggests that epistemic monitoring might be suppressed to some extent in narrative (as opposed to argumentative) texts. Future research should focus more explicitly on the conditions under which validation succeeds or fails, with the goal of reconciling evidence for readers' apparent susceptibility to false information with the abundant evidence for routine validation in language comprehension.…”
Section: Discussionmentioning
confidence: 97%
“…For example, it may be affected by the text genre (narrative vs. expository texts) or by the perceived credibility of a text source (encoding under distrust; e.g., Schul, Mayo, & Burnstein, 2004). For 22 ISBERNER AND RICHTER example, people seem to be particularly susceptible to false information and persuasion when reading or viewing narratives (e.g., Appel & Richter, 2007;Gerrig & Prentice, 1991;Green & Brock, 2000;Umanath, Butler, & Marsh, 2012), which suggests that epistemic monitoring might be suppressed to some extent in narrative (as opposed to argumentative) texts. Future research should focus more explicitly on the conditions under which validation succeeds or fails, with the goal of reconciling evidence for readers' apparent susceptibility to false information with the abundant evidence for routine validation in language comprehension.…”
Section: Discussionmentioning
confidence: 97%
“…But such work has nevertheless been informative. Empirical demonstrations have shown that individuals will rely on briefly presented inaccuracies to problematically complete summarization (e.g., Johnson & Seifert, ), judgment (e.g., Gerrig & Prentice, ; Appel & Richter, ; Rapp et al, ), recall (e.g., Andrews & Rapp, ; Butler, Zaromb, Lyle, & Roediger III, ; Ecker et al, ; Umanath, Butler, & Marsh, ), and questionnaire tasks (e.g., Marsh, ; Marsh et al, ; Marsh & Fazio, ). Overcoming these effects has not been trivial and has motivated thinking towards more mechanistic accounts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while reading about the Titanic , readers could be tasked with actively retrieving relevant memories about the historic event, which would presumably include information about how the Titanic fell victim to the iceberg collision. These tasks might not necessarily prove successful at changing moment‐by‐moment evaluative processes (see Rapp, ; Sparks & Rapp, ; Umanath et al, for discussions) but could support any subsequent considerations of the information for post‐reading tasks. Recent work from our own lab, for example, has shown that asking participants to carefully proofread text content can reduce their subsequent reliance on inaccurate text information (Rapp, Hinze, Kohlhepp, & Ryskin, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, everyday texts are potentially even more problematic than traditional lab‐based materials. Projects examining readers' reliance on inaccurate information have utilized stories that include incorrect facts without strong supportive contexts (but see Prentice, Gerrig, & Bailis, ; Umanath, Butler, & Marsh, ), unlike the extended, supportive contexts that can appear in everyday texts. Historical non‐fiction, for instance, is replete with cases in which authors set up circumstances that call into question well‐known facts, in the service of motivating interest in reading about familiar events.…”
mentioning
confidence: 99%